Mortality of European eel after downstream migration through two types of pumping stations. (27th August 2013) - Buysse, D.; Mouton, A. M.; Stevens, M.; Van, T.; Coeck, J.
Abstract Although numerous pumping stations (PS) have been used by water managers for numerous applications on rivers, canals and other water bodies, their impact on fish populations is poorly understood. This study investigates European eel, Anguilla anguilla (L.), mortality after natural downstream passage through a propeller pump and two Archimedes screw pumps at two PSs on two lowland canals in Belgium. Fyke nets were mounted permanently on the outflow of the pumps during the silver eel migration periods. Based on the condition and injuries, maximum eel mortality rates were assessed. Mortality rates ranged from 97 ± 5% for the propeller pump to 17 ± 7% for the large Archimedes screw pump and 19 ± 11% for the small Archimedes screw pump. Most injuries were caused by striking or grinding. The results demonstrate that PSs may significantly threaten escapement targets set in eel management plans.